Improved Performance of the Vapor Compression Cooling System Using A Combination of Condensers-Evaporative Cooling - Arfidian Rachman; Sulaeman Sulaeman; Syafrul Hadi (LP2M - Institut Teknologi Padang, 2018)
Energy use is a major problem in the vapor compression air cooling system, especially in areas with very hot weather conditions. In hot weather conditions, the performance of the system has decreased dramatically and electricity consumption has increased significantly. Combined Condensor with evaporative cooling will increase the heat removal process by using an evaporative cooling effect that will increase the efficiency of energy use. This paper presents the study of the use of evaporative cooling and condenser. This paper mainly calculated energy consumption in steam compression cooling systems and related problems. From the results of this study, the use of condensers with evaporative cooling, power consumption can be reduced to 46% and performance coefficient (COP) can be increased by about 12%, with 1,2 kW cooling capacity.